Perlindungan Hukum terhadap Konsumen Khusus Jasa Penumpang Angkutan Darat - Nyoman Gede Fajar Septiawan Putra; Desak Gede Dwi Arini; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2020)
Legal Protection is all businesses that bear the existence of legal provisions in providing protection to passengers or consumers who use the services of business operators to protect consumers from things that are not desirable. Public Transport Online is one of the public transportation media that is often used by the general public not only to transport passengers but to bring goods to be delivered to the destination address at a rate previously agreed. This study aims to analyze the factors that cause consumer losses for online transportation transport passengers and their protection in accordance with Law No. 8 of 1999 concerning Consumer Protection. This research was designed using the approach of Empirical Law research. The technique used in collecting data, namely the interview technique, was carried out at PT Aplikasi Karya Anak Bangsa. The results of this study indicate that the Online Public Transport Company is fully liable for losses caused by all people employed in public transport activities, besides online public transport companies and service carriers are fully obliged to sort out the compensation experienced by consumers and / or goods that can result disability and / or death, unless caused by an event that cannot be avoided or prevented due to passenger negligence. Through this research it is expected that consumers and service drivers must know each other's role and what their rights and obligations are so that it can reduce the loss for consumers or drivers of public transportation services.